Electrical Energy Saving Analysis in Educational Buildings Using CLTD and ECI Methods - Arrad Ghani Safitra; Lohdy Diana; Lovyta Putri Adianti; Naja Imama Mufidah (Infotekmesin, 2026)
An energy audit is a systematic assessment conducted to evaluate energy consumption and identify opportunities for improving energy efficiency in buildings. This study evaluates electrical energy consumption in three computer laboratories of the D3 PENS Building using the Energy Consumption Intensity (ECI) and Cooling Load Temperature Difference (CLTD) methods. The analysis was conducted based on measurements of room dimensions, indoor environmental conditions, electrical energy consumption, and cooling loads. The ECI values obtained for laboratories JJ-204, JJ-101, and JJ-310 were 24.44, 18.17, and 19.91 kWh/m²/month, respectively, indicating relatively high energy consumption. The CLTD analysis indicated that the cooling load was affected by external and internal heat gains, particularly those generated by occupants and computer equipment. The combined application of CLTD and ECI provides an assessment of the relationship between cooling load and electrical energy consumption. Energy conservation measures were proposed through operational adjustments, air-conditioning maintenance, and refrigerant replacement. The replacement of R-22 with MC-22 was estimated to reduce electricity consumption by 15.40%, corresponding to potential monthly savings of IDR 476,887.95. The study was limited to three computer laboratories under normal operating conditions and did not involve dynamic building energy simulation.